Meningkatkan Kemampuan Conversation pada Siswa Holiday Program Studi Kasus di Komunitas Kampung English Kudus - Muslimin; Stela Ramadhani Khalashinikov (Universitas Ngudi Waluyo, 2025)
Abstract English speaking ability is an essential skill for students in facing global challenges. This study aims to analyze the Improvement of Conversation Skills in Holiday Program Case Study Students in the Kudus English Village Community using the Collaborative Learning method. The research method used is a qualitative approach with the following research data collection techniques: 1) observation 2) interviews and 3) documentation. The subjects of the study were elementary school students who participated in the holiday program at the Kudus English Village during formal school holidays. The results showed that the Holiday Program had a positive impact on improving students' conversation skills. Students experienced an increase in speaking fluency, understanding of English, and self-confidence in communicating because it was also supported by the Collaborative Learning method where the learning environment became more interactive. Therefore, the Collaborative Learning-based Holiday Program can be an effective solution in improving English conversation skills for students during school holidays. Abstrak Kemampuan berbicara dalam bahasa Inggris merupakan keterampilan esensial bagi siswa dalam menghadapi tantangan global. Penelitian ini bertujuan untuk menganalisis Peningkatan Kemampuan Conversation pada Siswa Holiday Program Studi Kasus di Komunitas Kampung English Kudus dengan metode Collaborative Learning. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik pengumpulan data penelitian ini adalah: 1) observasi 2) wawancara dan 3) dokumentasi. Subjek penelitian yakni siswa usia Sekolah Dasar yang mengikuti program liburan (Holiday Program) di Kampung English Kudus ketika libur sekolah formal. Hasil penelitian menunjukkan bahwa Holiday Program memberikan dampak positif terhadap peningkatan keterampilan conversation siswa. Siswa mengalami peningkatan dalam kefasihan berbicara, pemahaman terhadap bahasa Inggris, serta rasa percaya diri dalam berkomunikasi karena didukung pula dengan metode Collaborative Learning dimana lingkungan belajar menjadi lebih interaktif. Oleh karena itu, Holiday Program berbasis Collaborative Learning dapat menjadi solusi efektif dalam meningkatkan keterampilan conversation bahasa Inggris bagi siswa selama liburan sekolah.